Decoding critical long non-coding RNA in ovarian cancer epithelial-to-mesenchymal transition - Ramkrishna Mitra (Nature Portfolio, 2017)
The role of lncRNA is unclear with respect to epithelial-to-mesenchymal transition (EMT), which is linked to ovarian cancer metastasis. Here, the authors show lncRNA DNM3OS expression contributes to ovarian cancer EMT, cell migration/invasion, and correlates with worse overall patient survival.